PENGARUH EVALUASI PROSES PEMBELAJARAN TERHADAP HASIL BELAJAR IPA DI MADRASAH IBTIDAIYAH - Shania Salsabila; Dadan Mardani; Iis Humaeroh (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Quantitative research is the approach employed in this study. Research methods that are based on the positivist philosophy and are utilized to examine specific populations or samples are known as quantitative research methods. Sampling techniques are typically carried out randomly, and data is collected using research instruments. Quantitative or statistical data analysis is then performed with the goal of testing established hypotheses. 50 grade 4 kids were observed, documented, and a questionnaire or questionnaire was utilized as the data gathering technique. Based on the frequency distribution table above, it can be seen that from the results of the legger scores that the author took from 50 students, as many as 29 students had good learning outcomes (58%) and 16 students had sufficient learning outcomes (32%) and 5 students whose learning outcomes were less (10%). From these data, it can be seen that the learning outcomes of MI Ma'had Al-Zaytun students in science lessons in grade 4 of the 2022-2023 school year are good. Based on the results of the regression test, the significance value is 0.009 < 0.05, which can be concluded that variable x has an influence on variable y, so that it can answer the formulation of the first problem that there is a relationship between the influence of the evaluation process on student learning outcomes. Keywords: Evaluation of the learning process, learning outcomes, Science, MI